Employment Relationship Interpretation for Informal Workers in Supreme Court Decision: Penafsiran Hubungan Kerja Pekerja Informal dalam Putusan Mahkamah Agung - Rahmawati, Qurnia; Nailul, Ahmad (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Employment relationships in Indonesian labor law are determined by cumulative elements of work, wages, and orders as the basis for legal protection. Specific Background: Supreme Court Decision Number 656 K/Pdt.Sus-PHI/2024 raises debate on the interpretation of these elements in the context of informal workers with flexible work patterns. Knowledge Gap: There is tension between a formalistic normative approach and the need for substantive legal protection for informal workers in modern labor dynamics. Aims: This study aims to analyze how the Supreme Court interprets the elements of work, wages, and orders and to examine its implications for labor law protection. Results: The Court interprets the elements strictly based on statutory provisions, concluding that wages are not fixed due to a ritase system, the element of orders is absent due to lack of subordination and work regulation, and work is not continuous or structurally integrated, leading to the classification of the relationship as a partnership rather than an employment relationship. Novelty: The study highlights a recent judicial decision within the evolving context of flexible work arrangements and informal labor classification. Implications: Although normatively consistent with labor regulations, the interpretation reflects a formalistic approach that potentially limits substantive legal protection for informal workers, indicating the need for more progressive legal interpretation oriented toward worker protection principles. Highlights• Strict cumulative interpretation determines legal classification as partnership• Flexible work patterns exclude recognition of normative wage structure• Formal legal reasoning constrains protection scope for non-formal labor KeywordsEmployment Relationship; Informal Workers; Legal Protection; Supreme Court Decision; Labour Law